Online alcohol sales and home delivery: An international policy review and systematic literature review. Issue 9 (September 2021) - Colbert, Stephanie; Wilkinson, Claire; Thornton, Louise; Feng, Xiaoqi; Richmond, Robyn
Highlights: 72 of 77 jurisdictions examined permit the online sale and home delivery of alcohol. Only 7 jurisdictions require age verification to occur at the time of purchase. 15 jurisdictions require that delivery drivers complete alcohol server training. 53 jurisdictions have relaxed alcohol home delivery regulations during COVID-19. Online alcohol retailer compliance with age restrictions is poor, ranging from 0 to 46%. Abstract: Background: Online alcohol sales are experiencing rapid growth in many places, accelerated by the COVID-19 pandemic, prompting new laws and regulations. There are no comprehensive and systematic analyses of the laws or their effectiveness. Objective: To summarise international policies governing online alcohol sale and delivery, including changes occurring with COVID-19, and examine available evidence of retailer compliance with such policies. Method: A policy review of 77 jurisdictions in six English-speaking OECD countries: United States, Canada, United Kingdom, Ireland, Australia and New Zealand. We synthesised policies according to ten elements identified as potentially relevant for public health regulation. A systematic literature review of compliance evaluations in Medline, Medline Epub, EMBASE, CINAHL, Web of Science and Google Scholar. Results: 72 of 77 jurisdictions permitted online alcohol sales and home delivery. Few jurisdictions require age verification at the time of purchase ( n = 7), but most require it at delivery ( n = 71). Since the COVID-19 pandemic began, most jurisdictions (69%) have either temporarily or permanently relaxed liquor regulations for alcohol home delivery. Three articles examined retailer compliance with age restrictions and found relatively low compliance (0%-46%). Conclusion: Many jurisdictions permit the online sale and delivery of alcohol, but regulation of these sales varies widely. In most, regulations do not meet the same standard as bricks-and-mortar establishments and may be insufficient to prevent youth access.